Tulsi plant in every Koli household - Mumbai Archive Project Team (Jio Institute, 2024)
Koli households commonly place the Tulsi planter at the entrance as a religious decoration. They come in a variety of materials, designs, and sizes. The plant is considered an earthly manifestation of the goddess Tulsi (or Vrinda), who is an avatar of Lakshmi, the goddess of wealth and the consort of Lord Vishnu. Therefore, the offering of Tulsi leaves is part of the ritual worship of Vishnu and his avatars, like Krishna and Vithoba.